An essay on Andean prosopography (Pongos and zoncitos) - Kapsoli Escudero, Wilfredo (2021)
Prosopography is the study of the most excluded beings in society. In this essay we rescue the life of Pongos y Zoncitos whose stories are forgotten with their invisible dreams. They with their sweat and blood fed the prosperity of the gamonales (parasitic plants that lived at the expense of good strains). The Pongos were serfs of the haciendas ignored and socially excluded. The zoncitos are enigmatic characters who act as buffoons to amuse the patrons and those close to them. Pongos and Zoncitos are also considered illas, that is, deities of good luck and abundance. They testify to their life with metaphors and allegories associated with time and nature. They also have utopian dreams and that at some point the world turns upside down.